β-Catenin Signaling Evokes Hair Follicle Senescence by Accelerating the Differentiation of Hair Follicle Mesenchymal Progenitors - Han, Jimin; Lin, Kaijun; Choo, Huiqin; He, Jia; Wang, Xusheng; Wu, Yaojiong; Chen, Xiaodong (Frontiers in Cell and Developmental Biology, 2022)
Understanding how to control fibroblast activation offers hope for the treatment of skin diseases. Wnt signaling controls multiple fibroblast subsets, with its excessive activity promoting the differentiation of hair follicle dermal stem cells (hfDSCs) and the hyperactivation of interfollicular fibroblasts. A new CD34CrePGR mouse line was generated. Through fate-tracing models and a series of β-catenin genetic experiments, combined with hair depilation, our study depicts how the wound environment increases phosphorylated β-catenin in hfDSCs and facilitates their differentiation into DP and dermal sheath (DS). In mice carrying hfDSCs-specific activate of β-catenin, hfDSCs accelerated their differentiation into DP cells. Notably, with the stabilization of β-catenin in CD34-expressing cells and potential activation of canonical Wnt signaling, the mutant mice showed a brief increase of hair density in the short term, but over time leads to a senescence phenotype developing premature canities and thinning (HF miniaturization). β-catenin signaling drove HF senescence by accelerating differentiation of CD34+ hfDSCs, resulting phenotypes are attributable to the differentiation of the hfDSC to dermal papilla (DP) cells and the loss of their stem cell potential. Therefore, our study reveals that the regulation of β-catenin signaling in hfDSCs may potentially become an important subject for future exploration in development of clinically effective therapies for hair loss treatment and an excellent model for revealing new therapeutic approaches to reverse aging or retarding the development of alopecia.